Innovative Work Behaviour in Local Government: Innovation Process and Gender Differences - Pradana, I Putu Yoga Bumi; Sayrani, Laurensius Petrus; Pah, Theny Intan Berlian Kurniati; Wijayanti, Nadia Sasmita; Saputra, Boni; Rijoly, Jacobus Cliff Diky (Magister Ilmu Administrasi Publik, 2025)
This research aims to identify and understand the barriers affecting public sector employees' innovative behaviors, particularly examining how these obstacles differ across stages of innovation and between genders. Utilizing a qualitative phenomenological approach, the research involved in-depth interviews with 40 informants from six agencies in Kupang City and Kupang Regency. Data were analyzed through thematic analysis techniques, revealing eleven major barriers categorized into political-administrative leadership, public management, and individual factors. Political-administrative barriers include insufficient support from political actors and a restrictive organizational climate. Public management challenges encompass a risk-averse culture, weak interdepartmental collaboration, limited knowledge sharing, bureaucratic constraints, and regulatory rigidity that restricts creative ideas perceived as